Screen printing of multi-mode emission NaYF4:Yb, Er(Tm)/NaYF4:Ce, Mn composites for anti-counterfeiting applications. (17th May 2021) - Liu, Wenjing; Zhang, Wenjun; Liu, Ruxin; Li, Guojing
Abstract : NaYF4 :Yb, Er(Tm)/NaYF4 :Ce, Mn composites were prepared by a hydrothermal method, and an anti-counterfeiting printed pattern can display different colors under different ambient lights. Abstract : The development of advanced luminescent materials with simple synthesis and a high safety factor is still a great challenge for anti-counterfeiting applications. Herein, multi-mode emission NaYF4 :Ln (Ln = Er/Tm, Yb/Er, Yb/Tm)/NaYF4 :Ce, Mn composites were synthesized by employing a hydrothermal method. These materials show an excitation source-dependent color change, and could show red, green and blue up-conversion (UC) luminescence under the irradiation of a 980 nm laser and exhibit green and blue down-conversion (DC) luminescence at 254 nm and 365 nm, respectively. The energy transfer mechanism of the UC and DC luminescence of the samples was discussed in detail. Moreover, the composite materials were further fabricated into fluorescent anti-counterfeit inks, and various multi-mode fluorescent patterns were created by screen printing technology. This work provides a simple and promising material with outstanding fluorescence properties for security and anti-counterfeiting applications.